Implementation of Project Based Learning based on Local Wisdom in Port Numbay Papua and its Impact on Students' Critical Thinking Skills - Putu Victoria M. Risamasu; Jan Pieter (Postgraduate, University of Mataram, 2024)
The education sector bears a significant duty to nurture a generation prepared for the period of Society 5.0; thus, systematic initiatives to foster analytical, critical, and creative thinking are essential. We refer to this cognitive approach as higher-order thinking Skills (HOTS). This research aims to develop science instructional materials using a project-based learning approach, rooted in the local wisdom of Port Numbay, and assess its influence on students' critical thinking skills concerning Earth's structure and surface content. We conducted Research and Development (R&D) on the 4D model, transforming it into a 3D format without a dissemination phase. The research sample comprised seventh-grade pupils from public junior high schools in Jayapura City. Five validators approved the developed physics teaching materials. We utilized a quasi-experiment with a randomized pretest-posttest control group design to assess the impact of the teaching materials. The research findings indicated that the created teaching materials positively influenced student outcomes, revealing significant disparities in critical thinking skills between students utilizing the developed materials and those employing traditional teaching methods. The designed instructional materials facilitate student learning transitions and enhance critical thinking skills due to their inherent ability to stimulate creativity, originality, and independence in scientific learning.